Endothelin-1 contributes to ischemia/reperfusion injury in isolated rat heart-attenuation of ischemic injury by the endothelin-1 antagonists BQ123 and BQ610. - Han, H; Neubauer, S; Braeker, B; Ertl, G (1995)
A potential detrimental role of endothelin-1 in myocardial ischemia/reperfusion injury was studied by use of the endothelin-1 antagonists BQ123 and BQ610. Isolated isovolumetric rat hearts were perfused at constant pressure. BQ123 (7 micrograms/min) and BQ610 (1.75 micrograms/min) did not alter mechanical function or coronary flow and shifted dose-response curves for endothelin-1 significantly to the right. In rats subjected to 30 min of no-flow ischemia, the increase of left ventricular resting pressure was significantly delayed by BQ123 and BQ610 compared to control (BQ123: 20 +/- 2* mmHg, BQ610: 19 +/- 2* mmHg, control: 44 +/- 4 mmHg at 15 min of ischemia, respectively, *P < 0.05 v control). With reperfusion after 30 min of ischemia, recovery of left ventricular developed pressure was not significantly affected but tended to be better with endothelin-1 antagonist pretreatment (BQ123: 20 +/- 3 mmHg; BQ610: 19 +/- 3 mmHg, control 12 +/- 3 mmHg). However, in hearts subjected to 15 min of ischemia followed by reperfusion, recovery of left ventricular developed pressure was improved by BQ610 pretreatment (BQ610: 52 +/- 8* mmHg, control: 24 +/- 6 mmHg). We conclude: BQ123 and BQ610 effectively antagonize the coronary constrictive effect of endothelin-1. BQ123 and BQ610 delay the development of contracture during ischemia and may improve functional recovery during reperfusion. Our findings suggest that endogenous endothelin-1 may contribute to ischemia/reperfusion injury.